Presence of carbamazepine, naproxen, and ibuprofen in wastewater from northern Tunisia. Issue 2 (3rd April 2019) - Khazri, Hassen; Ben Hassine, Sihem; Ghorbel–Abid, Ibtissem; Kalfat, Rafik; Trabelsi-Ayadi, Malika
Abstract: We investigated the occurrence of three pharmaceutical residues in four wastewater treatment plants (WWTPs) from northern Tunisia. The selected compounds were carbamazepine, naproxen, and ibuprofen; they are among the most commonly prescribed and widely used pharmaceutical agents worldwide. Samples (200 mL) were pre-concentrated using the solid phase extraction (SPE) enrichment procedure and the analysis of the pharmaceuticals was performed with high-performance liquid chromatography (HPLC-UV). The overall procedure provided limits of detection (LOD) lower than 0.5 µg.L −1 and recoveries of 78–97%. For the carbamazepine compound, the mean concentrations were 60.58, 93.19, and 132 µg.L −1 for the Bizerte, Jendouba, and Tunis WWTPs, respectively. This pharmaceutical was not detected in the Beja WWTPs. Naproxen and ibuprofens were not detected in the Jendouba WWTP but were found in the three other WWTPs with concentrations ranging from 2.94 to 36.17 µg.L −1 and from 8.02 to 43.22 µg.L −1, respectively. From the obtained data, it seems that these WWTPs are not able to eliminate this kind of micro-pollutants.